Tren Filantropi Modern: Inovasi dan Dampak Shadaqah Berbasis Digital pada Platfrom Crowdfunding Kitabisa.com - Izniyah, Izniyah; Rahmawati, Dwi Enjelina; Anggraini, Dyah Ayu Puji; Dinda Fahmi, Shurotul Mufarrida; Nawwaf, Mumtazun; Huda, Bakhrul (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Article History: Received: Revised: Accepted: Abstract: This research aims to analyze modern philanthropy trends related to innovation and the impact of digital-based shadaqah philanthropy on the Kitabisa.com crowdfunding platform so as to provide in-depth insight into the role and impact of digital-based shadaqah philanthropy on the Kitabisa.com crowdfunding platform in the context of modern philanthropy. The research method used is descriptive qualitative with a literature study approach. The type of data collected is secondary data obtained by summarizing findings from previous research that are relevant to the topic discussed. The results of this research discussion show that sadaqah philanthropy in the digital era can be a positive force and improve the quality of life of society more broadly through the use of crowdfunding platforms. This research also identifies the challenges and opportunities faced in optimizing the use of digital technology in the context of philanthropy. Regarding this, it can be concluded that the role and impact of digital shadaqah through the kitabisa.com crowdfunding platform has a significant positive impact on the benefit of the people. And also, it has a significant positive impact on the challenges and opportunities of digital technology in optimizing its use. By continuing to explore innovations to strengthen digital-based shadaqah philanthropy, it can be a sustainable solution to improve social conditions in the future. This research can be a valuable reference for further research that is closely related to the same topic. Keywords: Modern Philanthropy; Sadaqah Digital; Crowdfunding; Kitabisa.com